Prosper Mérimée's 'Federigo,' or How to Cheat God and Beat Pascal. - Cropper, Corry (Neophilologus, 2011)
Prosper Mérimée wrote 'Federigo' in 1829 and republished it in his 1833 collection Mosaïque. The story's protagonist, thanks to a rigged deck of cards, is able to defeat Death, the devil, and to ultimately cheat and gamble his way into heaven. With very few exceptions, scholars have either dismissed the story as derivative or have ignored it entirely. In this article I theorize an explanation for some of the differences between Mérimée's story and its folk-tale antecedents, consider why Mérimée selected this story to begin with, study the original details he added, and suggest why he added them. By combining faith, gambling, and a can't-lose wager, 'Federigo' calls to mind a fixture of the French philosophical tradition, namely Blaise Pascal's Pensées. Ultimately I argue that in 'Federigo' Mérimée creates a narrative that can be read as an attempt to undermine Blaise Pascal and his famous celestial wager.